Urgensi Etika di dalam Sistem Bisnis Islam - Khusniati Rofi'ah (Justicia Islamica, 2014)
Ethics concerns propriety, meaning what is appropriate or inappropriate for someone to do. If it relates to business, then the aspect of appropriateness is about what is appropriate or inappropriate for someone to do when running a business in order to make a profit. Business has several systems consisting of input supplies, processes and activities that produce outputs. The series of activities include production, distribution, capital, and marketing activities. All of these activities must be carried out in accordance with the applicable sharia rules, so that in running their business, a Muslim is not only worldly business oriented, but horizontally and vertically oriented. Therefore, business ethics is very necessary, especially Islamic ethics for Muslim entrepreneurs.